Influence of sustainability drivers and perception on intention towards sustainable entrepreneurship among small and medium enterprises (SMES) - Koe, Wei Loon (2015)
Entrepreneurial activities have contributed to both economic development and environmental degradation. Nowadays, business firms are urged to play a proactive role in rectifying environmental issues through sustainable entrepreneurship. In Malaysia, sustainable entrepreneurship is at its infancy stage; most of the small and medium enterprises (SMEs) regard sustainable entrepreneurship as something new and are not eagerly participated in it. Thus, as an initial step in developing sustainable entrepreneurs, this study was geared towards investigating the SMEs owner-managers’ intentions towards sustainable entrepreneurship and the antecedents of such intention. By integrating two popular intention-based models, i.e.: Entrepreneurial Event Model (EEM) and Theory of Planned Behavior (TPB), this study attempted to explain the formation of intention towards sustainable entrepreneurship through sustainability drivers and perceptions. A research framework and 32 hypotheses were constructed to guide this study. This research employed a quantitative research method. The data were collected from 404 SMEs in Malaysia through self-administered questionnaires. Subsequently, the data were analyzed using regressions models and Baron-Kenny approach. The results indicated that owner-managers of SMEs in Malaysia showed a rather high level of intention towards sustainable entrepreneurship. It was because many of them have heard about sustainability management and they have planned to practice it. As for the antecedents of intention, sustainability drivers and all the six components (i.e.: sustainability value, sustainability attitude, social norm, government legislation, time orientation and sustainability orientation) were proven significantly and positively related to intention. Therefore, the results supported TPB that both exogenous and endogenous factors influenced an individual’s intention. Meanwhile, this study also confirmed the partially mediating role of perception. The results verified that sustainability drivers indirectly influenced intention towards sustainable entrepreneurship through perception. Therefore, perception was confirmed as one of the factors that explained the process of how sustainability drivers led to intention towards sustainable entrepreneurship. The results also indicated the importance of developing a desirable and feasible perception in motivating SMEs to embark on sustainable entrepreneurship. This thesis contributed to the literature by confirming an integrative research model that explained the causal process of intention in regard to sustainable entrepreneurship. It also highlighted the factors that should be considered in forming intention towards sustainable entrepreneurship among SMEs. From the practical perspective, it showed that in promoting sustainable entrepreneurship among SMEs in Malaysia, developing the owner-managers’ intention is crucial at the beginning stage. Furthermore, in achieving Malaysia’s sustainability goals, it requires the efforts from both government and business operators.